Spurious Majority: The ‘Wrong Winner’ Result In The Thirteenth General Election Of Malaysia - Choo, Chean Hau (2018)
In the Thirteenth General Election of Malaysia in 2013, the ruling alliance won the general election via their victory in a majority of seats, but unprecedentedly they lost the popular vote to the opposition alliance. Such a result is known as ‘spurious majority’, ‘wrong winner’ result, or ‘perverse’ result which occurs when the winning party, coalition, or alliance wins the election even though coming second in terms of their national vote share. This study aims to, first, determine the causal factors of, and examine the ways these causal factors engender, spurious majority in Malaysia; and second, find out the relative impacts between systemic factors and proximate factors, and between institutional factors and reactive factors, on such a result.